Detection of seed DNA in regurgitates of granivorous carabid beetles. Issue 6 (14th August 2015) - Wallinger, C.; Sint, D.; Baier, F.; Schmid, C.; Mayer, R.; Traugott, M.
Abstract: Granivory can play a pivotal role in influencing regeneration, colonization as well as abundance and distribution of plants. Due to their high abundance, nutrient content and longevity, seeds are an important food source for many animals. Among insects, carabid beetles consume substantial numbers of seeds and are thought to be responsible for a significant amount of seed loss. However, the processes that govern which seeds are eaten and are therefore prevented from entering the seedbank are poorly understood. Here, we assess if DNA-based diet analysis allows tracking the consumption of seeds by carabids. Adult individuals of Harpalus rufipes were fed with seeds of Taraxacum officinale and Lolium perenne allowing them to digest for up to 3 days. Regurgitates were tested for the DNA of ingested seeds at eight different time points post-feeding using general and species-specific plant primers. The detection of seed DNA decreased with digestion time for both seed species, albeit in a species-specific manner. Significant differences in overall DNA detection rates were found with the general plant primers but not with the species-specific primers. This can have implications for the interpretation of trophic data derived from next-generation sequencing, which is based on the application of general primers. Our findings demonstrate that seed predation by carabids can be tracked, molecularly, on a species-specific level, providing a new way to unravel the mechanisms underlying in-field diet choice in granivores.